The right to retaliate under the WTO Agreement : the 'sequencing' problems - Valles, Cherise M. (2000)
Examines the provisions of the WTO Agreement applicable to the determination of compliance and the suspension of concessions, and highlights the interpretive problems they raise. Considers the opposing positions adopted by the United States and the EC on these issues during the Banana Dispute. Examines the alternative approaches taken by countries in other disputes. Reviews the proposal to amend the Dispute Settlement Understanding.